Renal Impairment in Patients With Multiple Myeloma: A Consensus Statement on Behalf of the International Myeloma Working Group - Dimopoulos, Meletios A.; Terpos, Evangelos; Chanan-Khan, Asher; Leung, Nelson; Ludwig, Heinz; Jagannath, Sundar; Niesvizky, Ruben; Giralt, Sergio; Fermand, Jean-Paul; Bladé, Joan; Comenzo, Raymond L.; Sezer, Orhan; et al. (Journal of clinical oncology, 2010)
Renal impairment is a common complication of multiple myeloma (MM). The estimated glomerular filtration rate (eGFR) using the Modification of Diet in Renal Disease formula is the recommended method for the assessment of renal function in patients with MM with stabilized serum creatinine. In acute renal injury, the RIFLE (risk, injury, failure, loss and end-stage kidney disease) and Acute Renal Injury Network criteria seem to be appropriate to define the severity of renal impairment. Novel criteria based on eGFR measurements are recommended for the definition of the reversibility of renal impairment. Rapid intervention to reverse renal dysfunction is critical for the management of these patients, especially for those with light chain cast nephropathy. Bortezomib with high-dose dexamethasone is considered as the treatment of choice for such patients. There is limited experience with thalidomide in patients with myeloma with renal impairment. Thus, thalidomide can be carefully administered, mainly in the context of well-designed clinical trials, to evaluate if it can improve the rapidity and probability of response that is produced by the combination with bortezomib and high-dose dexamethasone. Lenalidomide is effective in this setting and can reverse renal insufficiency in a significant subset of patients, when it is given at reduced doses, according to renal function. The role of plasma exchange in patients with suspected light chain cast nephropathy and renal impairment is controversial. High-dose melphalan (140 mg/m 2 ) and autologous stem-cell transplantation should be limited to younger patients with chemosensitive disease.